2006
DOI: 10.1136/tc.2003.007237
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to the peer influence paradigm: results for 12–13 year olds from six European countries from the European Smoking Prevention Framework Approach study

Abstract: Objective:To examine whether smoking onset in young adolescents is predicted by peer or parental smoking.Design:Longitudinal design with one pretest and one follow-up at 12 months.Setting:Schools in Finland, Denmark, the Netherlands, the United Kingdom, Spain and Portugal.Participants:7102 randomly selected adolescents from six countries. Mean age was 12.78 years.Main outcome measures:Smoking behaviour of adolescents, peers and parents.Results:No support was found for peer smoking as an important predictor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
3
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(110 citation statements)
references
References 52 publications
10
90
3
7
Order By: Relevance
“…When family influence is compared to that of friends, the estimates from our study indicate that the influence of friends is stronger. Similar findings have been reported in a previous study, and a possible explanation is that peer influence on smoking behaviors appears to be more important during adolescence 15,24 . Besides, a recent Finnish study suggested that the most common source for e-cigarettes was friends, which may also partly explain the observed stronger influence of friends 13 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…When family influence is compared to that of friends, the estimates from our study indicate that the influence of friends is stronger. Similar findings have been reported in a previous study, and a possible explanation is that peer influence on smoking behaviors appears to be more important during adolescence 15,24 . Besides, a recent Finnish study suggested that the most common source for e-cigarettes was friends, which may also partly explain the observed stronger influence of friends 13 .…”
Section: Discussionsupporting
confidence: 78%
“…Besides, a recent Finnish study suggested that the most common source for e-cigarettes was friends, which may also partly explain the observed stronger influence of friends 13 . However, considering that adolescent smokers choose friends with similar smoking behaviors 24 , the peer influence in dual users (i.e. those who use cigarettes and e-cigarettes) should be interpreted with caution, and further longitudinal studies with nonsmoking adolescents are warranted to examine this proposition.…”
Section: Discussionmentioning
confidence: 99%
“…Two main mechanisms can explain peer infl uence, namely peer pressure and peer selection ( Hoffman, Monge, Chou, & Valente, 2007 ). Individual characteristics, like sensation seeking, might determine the selection of friends, who then provide a peer context that may or may not encourage smoking experimentation ( Arnett, 2007 ;de Vries, Candel, Engels, & Mercken, 2006 ) or may convey the reinforcement expectancies. The present study and other studies support that perceived peer smoking mediates between sensation seeking and smoking ( Wills et al, 1998 ;Yanovitzky, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant aspects of the school environment that could contribute to the development of smoking include school smoking policies, affiliation with deviant peers, and economic status. 61,62 Evidence that smokers have shortened educational careers raises the possibility of a reciprocal effect of educational achievements and smoking behaviours over time. 63,64 Inequalities in smoking by educational attainment are a major contributor to educational inequalities in mortality.…”
Section: Limitationsmentioning
confidence: 99%